2021
DOI: 10.1111/add.15450
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of four smoking behaviors using partitioned SNP heritability

Abstract: Background and Aims Although genome-wide association studies have identified many loci that influence smoking behaviors, much of the genetic variance remains unexplained. We characterized the genetic architecture of four smoking behaviors using single nucleotide polymorphism (SNP) heritability (h 2 SNP ). This is an estimate of narrow-sense heritability specifically estimating the proportion of phenotypic variation due to causal variants (CVs) tagged by SNPs. Design Partitioned h 2 SNP analysis of smoking beha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…The influence phenotypic scaling was reported in recent study of Evans et al 2021 where CigDay showed higher heritability when it was dichotomized versus the ordinal version analyzed here 52 . Estimation of heritability for binned variable (e.g., CigDay in this study) may be improved by different modeling choice including liability threshold model 54 .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The influence phenotypic scaling was reported in recent study of Evans et al 2021 where CigDay showed higher heritability when it was dichotomized versus the ordinal version analyzed here 52 . Estimation of heritability for binned variable (e.g., CigDay in this study) may be improved by different modeling choice including liability threshold model 54 .…”
Section: Discussionsupporting
confidence: 69%
“…AgeSmk tended to show higher rare variant heritability when extreme observations were included than they were not. Extreme observations may induce model misspecification or alternatively, are enriched in causal rare variants, possibly leading to higher heritability estimates 23,52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Under this scenario smoking status would be capturing smoking associated variants, and the genome-by-smoking interaction would represent GxG instead of GxE. However, given the relatively small heritability of tobacco smoking (SNP heritability ~18% 45 ), it is unlikely that all the variation we detected is driven by GxG.…”
Section: Discussionmentioning
confidence: 96%
“…Tobacco use causes signi cant global mortality and morbidity, contributing to several systemic conditions, including cardiometabolic diseases and cancers 1,2 . Tobacco use has historically been studied as an environmental risk factor for other diseases; however, tobacco use could instead be viewed as a complex psychiatric trait with environmental risk factors 3 and signi cant genetic contributions 4,5 . Multiancestry genetic studies report an estimated heritability (i.e., the proportion of the phenotypic variance explained by genetics) of tobacco use behaviors ranging between 5-18% 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco use has historically been studied as an environmental risk factor for other diseases; however, tobacco use could instead be viewed as a complex psychiatric trait with environmental risk factors 3 and signi cant genetic contributions 4,5 . Multiancestry genetic studies report an estimated heritability (i.e., the proportion of the phenotypic variance explained by genetics) of tobacco use behaviors ranging between 5-18% 4,5 . Prevention and management strategies for tobacco use can bene t from precision medicine approaches, with the inclusion of baseline genetic risk to develop individualized preventive and therapeutic strategies for tobacco use.…”
Section: Introductionmentioning
confidence: 99%